Pharmacogenomics in cardiovascular disorders: Steps in approaching personalized medicine in cardiovascular medicine - Christopher Barone; Shaymaa S Mousa; Shaker A Mousa (Dove Medical Press, 2009)
Christopher Barone, Shaymaa S Mousa, Shaker A MousaThe Pharmaceutical Research Institute, Albany College of Pharmacy and Health Sciences, Albany, NY, USAAbstract: Some of the most commonly prescribed medications are those for cardiovascular maladies. The beneficial effects of these medications have been well documented. However, there can be substantial variation in response to these medications among patients, which may be due to genetic variation. For this reason pharmacogenomic studies are emerging across all aspects of cardiovascular medicine. The goal of pharmacogenomics is to tailor treatment to an individual’s genetic makeup in order to improve the benefit-to-risk ratio. This review examines the potential pharmacogenomic parameters which may lead to a future of personalized medicine. For example, it has been found that patients with CYP2C9 and VKORC1 gene variations have a different response to warfarin. Other studies looking at β-blockers, ACE inhibitors, ARBs, diuretics and statins have shown some results linking genetic variations to pharmacologic response. However these studies have not impacted clinical use yet, unlike warfarin findings, as the small retrospective studies need to be followed up by larger prospective studies for definitive results.Keywords: cardiovascular, pharmacogenomics, genetics, cardiovascular medicine, personalized medicine, polymorphism